Enhancing the Level of Awareness on Healthy Lifestyles among Seventh-Grade Students - Isnani, Mufidah; Astuti, Dhesi Ari; Romero, Cyril B. (The Indonesian Institute of Science and Technology Research, 2024)
This study investigates the level of knowledge on healthy lifestyles among seventh-grade students at a public junior school in Yogyakarta, Indonesia. Utilizing quantitative descriptive research, data was collected through a questionnaire administered to 64 students. Analysis revealed a varied distribution of knowledge levels, with 53.1% demonstrating sufficient understanding, and 9.4% exhibiting limited knowledge. The findings underscore the importance of improving health education to empower students to make informed decisions. Collaborative efforts with Community Health Centers and implementation of healthy living initiatives are recommended to enhance students' health literacy and promote healthier lifestyles. These findings contribute to the ongoing discourse on enhancing health education among youth, with implications for promoting well-being and positive health outcomes.